PENGARUH IKLIM ORGANISASI, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA (Studi Kasus Pada Pegawai Kantor Kelurahan Pedurenan, Kota Tangerang): Fakultas Ekonomi dan Bisnis, Universitas Budi Luhur Jakarta - Azzahra, Kamila Rachmania; Wahyudi, Widi (PT. Media Edutama Nusantara, 2024)
This study aims to thoroughly investigate the impact of Organizational Climate, Work Motivation, and Work Environment on Work Productivity among employees at the Pedurenan Village Office, Tangerang City. A comprehensive quantitative approach is used in this research, with all employees at the village office being the population. The necessary data was collected using a questionnaire and then carefully analyzed using IBM SPSS version 22 software. This study proves that Organizational Climate and Work Environment are important factors that significantly influence Work Productivity. On the other hand, Work Motivation is not proven to be a determining factor in Work Productivity.